New roadmap for proactive livestock management in East Africa - International Livestock Research Institute (International Livestock Research Institute, 2025)
This blog highlights a regional initiative led by the International Livestock Research Institute (ILRI) to transition East Africa’s livestock sector from reactive crisis management to data-driven resilience. Collaborating with technical experts and policymakers from Kenya, Ethiopia, Uganda, and Tanzania, the strategy employs advanced geospatial technology and earth observation data to assess livestock vulnerability across three pillars: exposure to climate stressors, sensitivity of systems, and adaptive capacity.